2008
DOI: 10.1007/978-1-84800-207-4_7
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Users from Online Grocery Stores

Abstract: Grocery shopping, traditionally considered as the pinnacle of the selfservice industry, is used as the case study in this chapter. As the Internet has become widely used by many segments of the population, the opportunity to shop online for groceries has been presented to consumers. This chapter considers issues that need to be addressed to make online grocery shopping systems more usable for these consumers, based on feedback from individuals who participated in a study of user interactions with Australian on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…HB is the only variable that is significant across all samples: It is the most important determinant of BI for users, the second most important for potential adopters, and the third most important for all respondents. This is not surprising as grocery shopping is a routinized and habitual task [114,115]. The relationship between HB and BI has also been found to be significant in an emerging country context, at least for potential adopters [32].…”
Section: Discussionmentioning
confidence: 99%
“…HB is the only variable that is significant across all samples: It is the most important determinant of BI for users, the second most important for potential adopters, and the third most important for all respondents. This is not surprising as grocery shopping is a routinized and habitual task [114,115]. The relationship between HB and BI has also been found to be significant in an emerging country context, at least for potential adopters [32].…”
Section: Discussionmentioning
confidence: 99%
“…First, previous research has found shopper profiles differ between the two channels, and so one would need to disentangle shopper type from shopping mode. Some studies have suggested men prefer online shopping more than women (Souitaris and Balabanis, ; Wood, ), but many others have found online purchasing skews towards women (Freeman, ; Hand et al, ; Montgomery et al, ; Morganosky and Cude, ; Raijas, ). The varied results arise because some studies such as Wood () ask about preference for shopping mode, while others examine the actual proportions of each gender that buy online (e.g.…”
Section: Background Literature Review and Research Propositionsmentioning
confidence: 99%
“…Online retailing is revolutionizing the retail landscape (Wood, 2011) with over three-quarters of all United Kingdom (UK) citizens have purchased goods online (Office for National Statistics, 2015). After a slow adoption by apparently hesitant consumers (Elliot and Fowell, 2000; Freeman, 2009; Geuens et al, 2003; Pavitt, 1997; Ramus and Nielsen, 2005) online sales grew from $1B in 1995 (Lohse and Spiller, 1998; Schmid et al, 1996) to almost $2T in 2016 (eMarketer, 2016). Today, online retail accounts for just over 8% of all retail sales and is projected to increase to around 14% by 2020 (Business Wire, 2016; eMarketer, 2016).…”
Section: Introductionmentioning
confidence: 99%